2018
DOI: 10.1002/jcad.12189
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Child Parent Relationship Therapy for Adoptive Families: A Replication Study

Abstract: This randomized controlled replication study examined the effectiveness of child parent relationship therapy (CPRT) with 49 adoptive families. Statistically significant improvement and large treatment effects for child behavior problems, parent–child relationship stress, and parents' empathic interactions with their children indicated the effectiveness of CPRT over treatment as usual. Findings confirm Carnes‐Holt and Bratton's () results and provide strong support for CPRT as a responsive intervention for adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…CPRT helped to equip parents with new ways to respond to and interact with their preadolescent children, supporting their continually growing relationship. As anticipated, these findings also support the recommendations made by Carnes-Holt and and Opiola and Bratton (2018) to extend the CPRT model to include a greater number of sessions for families with higher needs, such as many adoptive families who report attachment and behavioral concerns.…”
Section: Discussionsupporting
confidence: 84%
“…CPRT helped to equip parents with new ways to respond to and interact with their preadolescent children, supporting their continually growing relationship. As anticipated, these findings also support the recommendations made by Carnes-Holt and and Opiola and Bratton (2018) to extend the CPRT model to include a greater number of sessions for families with higher needs, such as many adoptive families who report attachment and behavioral concerns.…”
Section: Discussionsupporting
confidence: 84%
“…The theme of relationship components and its subthemes (boundaries, attachment, challenge to relate, trust, and fear) directly relate to outcomes demonstrated in CPRT research. Research demonstrates that CPRT participation among adoptive parents can result in significant improvement in parental empathy, which relates to relationship components that were indicated as reasons for self-referral in the present study (Carnes-Holt & Bratton, 2014;Opiola & Bratton, 2018;Swan et al, 2019). The theme of parenting considerations associated with seeking out services, along with included subthemes (parenting characteristics, parenting stress, parenting styles, and parent coping) also relate to outcomes established in CPRT research.…”
Section: Figurementioning
confidence: 58%
“…Carnes-Holt and Bratton's (2014) findings indicated that CPRT participation resulted in significant improvement in adopted youths' use of externalizing behaviors, similar to behaviors described and characterized as child factors in this study. Opiola and Bratton (2018) and Swan et al (2019) also found that adoptive parents' participation in the CPRT intervention resulted in significant improvements in child problem behaviors over time. Findings from Socarras et al's (2015) qualitative study demonstrated that parents perceive social support and acceptance through CPRT's group process element, which relates to the theme of adoption experiences and its subthemes (needing support, expectations vs. reality, adoption process, and family dynamics) in the present study.…”
Section: Figurementioning
confidence: 93%
“…However, there continues to be limited mention or discussion on adaptations for parents and children with disabilities. CPRT has been adapted to work with toddlers (Bennett & Carnes-Holt, 2019), preadolescents (Ceballos et al, 2019;Swan et al, 2019), and adoptive families (Carnes-Holt, 2010;Carnes-Holt & Opiola, 2019;Opiola & Bratton, 2018;Swan et al, 2019). Additionally, CPRT has been expanded to incorporate teachers (Helker & Bennett, 2019;Morrison & Helker, 2010) and provided a culturally responsive approach to working with children of color with different cultural backgrounds (Sheely-Moore et al, 2019;Vandergast et al, 2010).…”
Section: Cprtmentioning
confidence: 99%
“…Child-parent-relationship therapy (CPRT) is an evidencebased approach for working with families that focuses on enhancing the parent-child attachment while lowering parental stress (Lin & Bratton, 2015). Adaptations to CPRT as a model has been supported by research to include diverse family systems in a culturally responsive manner (e.g., Ceballos & Bratton, 2010;Opiola & Bratton, 2018;Sheely-Moore & Bratton, 2010). Based on empirical evidence, CPRT has demonstrated having a positive impact on parent-child relationship.…”
mentioning
confidence: 99%